Effects of low doses of hydrochloride tetracycline on bone metabolism and uterus in ovariectomized rats. - Li Qing-Nan; Hu Bin; Huang Lian-Fang; Chen Yan; Weng Ling-Ling; Zheng Hu; Chen Huai-Qing (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of low doses of hydrochloride tetracycline (Tc) on bone metabolism and uterus in the ovariectomized (Ova) rats. METHODS: Forty 3-month-old rats were randomly divided into 5 groups: sham group, Ova group, Tc1 group (1.2 mg/kg/d), Tc2 group (4.8 mg/kg/d), and estrone group (1.48 mg/kg/d), oral fed for 3 months. The proximal tibia metaphyses were processed undecalcified for quantitative bone histomorphometry and the soft tissues were processed in paraffin for pathological observation. RESULTS: Placebo-treated (lactose) Ova rats were characterized by trabecular area (TA) decreasing and their architecture worsening compared with sham controls, and bone resorption was over formation with high bone turnover. The uteri were atrophy. (2) In estrone-treated group, TA and trabecular numbers were significantly increased and the trabecular separation decreased vs Ova group. Estrone slowed down Ova-inducing bone high turnover. But the size, weight, and the endometrium of the uteri in this group were increased vs Ova group. (3) TA was increased in both Tc1 and Tc2 groups compared with Ova rats. Tc maintained bone formation indices almost at Ova level, and only decreased mineral apposition rate (MAR) in Tc1 group, and declined bone resorption perimeter. The uteri and the cell of liver and kidney almost maintained at Ova level; Tc2 decreased labeling perimeter and increased MAR in comparison with Tc1 group. The uteri were atrophy, whose size maintained at Ova level; yellow labeling was not found in bone with these doses of Tc, while yellow labeling could be seen with the doses of 30 mg/kg/d of Tc for bone marker. CONCLUSION: The two doses of Tc have similar effects on preventing bone loss in Ova rats while the bone formation and uterus are not affected. However, Tc2 does not have more effects on increasing bone mass, Tc2 causes less mild damages to the liver and kidneys.